Mencermati Perilaku Kekerasan dan Paradigma Sosial - Dian Wahyuni P. (Unisia, 2006)
The effect of violence action toward victims that undergoes more is traumatically experience. This experience is difficult to lose from the victims. In this sense, the problems will be followed by other problems either physically, psychologically, or those of social. The above effect is experienced more with stigma, that tends to make the victims to be introvert, etc. Besides, society tend to sentence the victims, so does information media without empathy and private appreciation publishes the violence cases clearly. However, the violence is something to be sentenced. There is no nation in the world has right to conduct the violence action.